A new species of gregarious Meteorus (Hymenoptera: Braconidae) reared from caterpillars of Venadicodia caneti (Lepidoptera: Limacodidae) in Costa Rica - Shaw, Scott R.; Nishida, Kenji (Zootaxa, 2005)
A new species of parasitoid wasp, Meteorus oviedoi Shaw and Nishida (Hymenoptera: Braconidae), is described from the Central Valley of Costa Rica. The new species is diagnosed and compared to other species in the genus. It was reared from larvae of Venadicodia caneti (Lepidoptera: Limacodidae) on leaves of Licaria triandra (Lauraceae). The parasitoid is gregarious and modifies the behavior of its host. This is the first record of a Meteorus species attacking Limacodidae in Costa Rica.Una nueva especie, Meteorus oviedoi Shaw and Nishida (Hymenoptera: Braconidae) es descrita para Valle Central de Costa Rica. La especie es analizada y comparada con otras especies del género. Los especimenes fueron criados de larvas de Venadicodia caneti (Lepidoptera: Limacodidae), encontradas en hojas de Licaria triandra (Lauraceae). El parasitoide es gregario y modifica comportamiento del hospedero.